Prevalence of glomerulopathies in canine mammary carcinoma - Crivellenti, Leandro Z. [UNESP]; Silva, Gyl E.B.; Borin-Crivellenti, Sofia [UNESP]; Cianciolo, Rachel; Adin, Christopher A.; Dantas, Márcio; Dos Anjos, Denner S.; Tinucci-Costa, Mirela [UNESP]; Santana, Aureo E. [UNESP] (Public Library of Science (PLoS), 2016)
The incidence and prevalence of paraneoplastic glomerulopathy, especially associated with carcinoma, are a matter of debate and the causal link between cancer and glomerular diseases remains unclear. The aim of this study was to evaluate renal biopsies of selected bitches with spontaneous mammary gland carcinoma. We hypothesized that dogs with mammary carcinomas would show histologic evidence of glomerular pathology. A prospective study was performed in dogs with naturally occurring mammary carcinoma that were undergoing tumor resection and ovariohysterectomy. We evaluated renal biopsies of 32 bitches with spontaneous mammary gland carcinoma and 11 control dogs without mammary gland neoplasia. Samples were obtained from the left kidney and the biopsy material was divided for light microscopy (LM), immunofluorescence (IF) and transmission electron microscopy (TEM). Light microscopy abnormalities were identified in 78.1% of dogs with mammary carcinoma (n = 25) and in none of the dogs in the control group. Focal glomerular mesangial matrix expansion was the most common alteration (n = 15, 60.0%), but mesangial cell proliferation (n = 9, 36.0%) and focal segmental glomerulosclerosis (n = 9, 36.0%), synechiae (n = 7, 28.0%), and globally sclerotic glomeruli (n = 6, 24.0%) were also frequent in dogs with malignancy. Immunofluorescence microscopy revealed strong IgM staining was demonstrated in 64.3% (n = 18) of carcinoma dogs. Transmission electron microscopy from dogs with carcinoma revealed slight changes, the most frequent of which was faint sub-endothelial and mesangial deposits of electron-dense material (78%). Mesangial cell interpositioning and segmental effacement of podocyte foot processes were identified in some specimens (45%). Changes in the glomerulus and proteinuria are common in dogs with naturally occurring mammary carcinoma and this condition appears to provide an excellent large animal model for cancer-associated glomerulopathy in humans.